Phase-Sensitive Optical Time-Domain Reflectometer Based on a 120°-Phase-Difference Michelson Interferometer*Supported by the National Natural Science Foundation of China under Grant Nos U0934001 and 11076028, the Science and Technology Commission of Shanghai Municipality under Grant Nos 11DZ1140202 and 13XD1425400, and the Pudong New Area Science and Technology Development Fund of China under Grant No PKJ2012-D04. (May 2016) - Cao 曹, Yu-Long 玉龙; Yang 杨, Fei 飞; Xu 徐, Dan 丹; Ye 叶, Qing 青; Cai 蔡, Hai-Wen 海文; Fang 方, Zu-Jie 祖捷
Abstract : A phase-sensitive optical time domain reflectometer (φ-OTDR) based on a 120°-phase-difference Michelson interferometer is proposed. The Michelson interferometer with arm difference of 4m is used to test the phase difference between the Rayleigh scattering from two sections of the fiber. A new demodulation method called the inverse transmission matrix demodulation scheme is utilized to demodulate the distributed phase from the backward scattering along the long fiber. The experimental results show that the 120°-phase-difference interferometer φ-OTDR can detect the phase along the 3km fiber, and the acoustic signal within the whole human hearing range of 20 Hz–20 kHz is reproduced accurately and quickly.